2021
DOI: 10.1101/2021.07.23.453522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nano-Insecticides Against the Black Cutworm Agrotis ipsilon (Lepidoptera: Noctuidae): Toxicity, Development, Enzyme activity, and DNA Mutagenicity

Abstract: High-frequency doses of chemical pesticides cause environmental pollution with high pesticide residues. In addition, increasing insecticide resistance in many insect pests requires novel pest control methods. Nanotechnology could be a promising field of modern agriculture, and is receiving considerable attention in the development of novel nano-agrochemicals, such as nanoinsectticides and nanofertilizers. This study assessed the effects of the lethal and sublethal concentrations of chlorantraniliprole, thiocyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Data analysis showed that the LC50 (that kills 50% of larvae population) of Se-NPs was ranging between 2.9-4.2 ppm for different instar larvae, whereas the LC90 (that kills 90% of larvae population) was ranging between 5.1-7.5 ppm. Similarly, the LC50 for nano-chlorantraniliprole and nano-thiocyclam against A. ipsilon were 0.015 and 4.46 mg L -1 which showed higher toxicity than bulk material [73].…”
Section: Larvicidal Activitymentioning
confidence: 94%
“…Data analysis showed that the LC50 (that kills 50% of larvae population) of Se-NPs was ranging between 2.9-4.2 ppm for different instar larvae, whereas the LC90 (that kills 90% of larvae population) was ranging between 5.1-7.5 ppm. Similarly, the LC50 for nano-chlorantraniliprole and nano-thiocyclam against A. ipsilon were 0.015 and 4.46 mg L -1 which showed higher toxicity than bulk material [73].…”
Section: Larvicidal Activitymentioning
confidence: 94%
“…The indiscriminate use of conventional and newer insecticides has caused the development of resistance to almost all kinds of insecticides in the Noctuidae species Fouad et al, (2022), Zhang et al, (2022), Garlet et al, (2021), Awad et al, (2022). Therefore, monitoring insecticides is considered a pre-requisite in IPM programs (Bull and Men 1990) and becomes a remarkable aspect of resistance management Abo- Elghar et al, (2005).…”
Section: Indoxacarbmentioning
confidence: 99%